IMPROVING TEACHERS’ PROFESSIONAL PERFORMANCE IN AGUATA LOCAL GOVERNMENT AREA: PROBLEMS & PROSPECTS - V. N., Eboatu,; Matthew, Ozigbo, Ekene (European Scientific Journal, ESJ, 2015)
The problem of falling standards in the educational achievements of students, especially in external examinations has led to criticism of teachers and the teaching profession. This study therefore was designed to determine the problems that militate against proper admission, recruitment, training and retention of qualified teachers and the prospects for improved teacher performance in Aguata Local Government Area of Anambra State, Nigeria. Three research questions guided the study which adopted the descriptive survey design. The total population of this study consisted of seventy-two (72) educational administrators. There was no sample for the study because the population was small and manageable. A structured questionnaire was used for data collection, while the mean statistical analysis was employed to answer the research questions. The result showed that entry into Teacher Education Institutions and recruitment into the Teaching Service were not regulated and that retraining of teachers for continuing development was not undertaken. Based on the findings, the researchers recommended amongst other things, that entry into the profession be regulated, the curricula of Teacher Education Institutions be reviewed and upgraded and that teacher’s Mandatory Continuing Professional Development be institutionalized.